Sonographische Differenzialdiagnostik fokaler Leberläsionen - Zundler, Sebastian; Strobel, Deike (Die Gastroenterologie, 2023)
Rapid diagnostic assessment is crucial for the clinical management of focal liver lesions. In addition to standard B-mode sonography, color-coded Doppler sonography and contrast-enhanced ultrasound are widely used for the classification of liver tumors. In gastroenterology, clinical sonography plays an important role in the detection of tumors, in the follow-up of oncological patients and for the screening for hepatocellular carcinoma. Thereby, correctly classifying focal liver lesions essentially requires the interpretation of ultrasound findings in the clinical context (e.g., incidental finding, known risk factors, history of liver cirrhosis or malignant disease). In this review, we summarize the available ultrasound techniques for the characterization of focal liver lesions and discuss their importance and relevance for the differential diagnosis and further diagnostic and therapeutic management.
CRIS-Team WoS Importer:2023-03-03